Myocardial blood flow in patients with low-flow, low-gradient aortic stenosis: differences between true and pseudo-severe aortic stenosis. Results from the multicentre TOPAS (Truly or Pseudo-Severe Aortic Stenosis) study. Issue 12 (1st April 2008) - Burwash, I G; Lortie, M; Pibarot, P; de Kemp, R A; Graf, S; Mundigler, G; Khorsand, A; Blais, C; Baumgartner, H; Dumesnil, J G; Hachicha, Z; DaSilva, J; et al.
Abstract : Background: Impairment of myocardial flow reserve (MFR) in aortic stenosis (AS) with normal left ventricular function relates to the haemodynamic severity. Objectives: To investigate whether myocardial blood flow (MBF) and MFR differ in low-flow, low-gradient AS depending on whether there is underlying true-severe AS (TSAS) or pseudo-severe AS (PSAS). Methods: In 36 patients with low-flow, low-gradient AS, dynamic [13 N]ammonia PET perfusion imaging was performed at rest (n = 36) and during dipyridamole stress (n = 20) to quantify MBF and MFR. Dobutamine echocardiography was used to classify patients as TSAS (n = 18) or PSAS (n = 18) based on the indexed projected effective orifice area (EOA) at a normal flow rate of 250 ml/s (EOAIproj ⩽ or >0.55 cm 2 /m 2 ). Results: Compared with healthy controls (n = 14), patients with low-flow, low-gradient AS had higher resting mean (SD) MBF (0.83 (0.21) vs 0.69 (0.09) ml/min/g, p = 0.001), reduced hyperaemic MBF (1.16 (0.31) vs 2.71 (0.50) ml/min/g, p<0.001) and impaired MFR (1.44 (0.44) vs 4.00 (0.91), p<0.001). Resting MBF and MFR correlated with indices of AS severity in low-flow, low-gradient AS with the strongest relationship observed for EOAIproj ( r s  = −0.50, p = 0.002 and r s  = 0.61, p = 0.004, respectively). Compared with PSAS, TSAS had a trend to a higher resting MBF (0.90 (0.19) vs 0.77 (0.21) ml/min/g, p = 0.06), similar hyperaemic MBF (1.16 (0.31) vs 1.17 (0.32) ml/min/g, p = NS), but a significantly smaller MFR (1.19 (0.26) vs 1.76 (0.41), p = 0.003). An MFR <1.8 had an accuracy of 85% for distinguishing TSAS from PSAS. Conclusions: Low-flow, low-gradient AS is characterised by higher resting MBF and reduced MFR that relates to the AS severity. The degree of MFR impairment differs between TSAS and PSAS and may be of value for distinguishing these entities.